2014
DOI: 10.2337/db13-0788
|View full text |Cite
|
Sign up to set email alerts
|

Vanin-1 Is a Key Activator for Hepatic Gluconeogenesis

Abstract: Vanin-1 (VNN1) is a liver-enriched oxidative stress sensor that has been implicated in the regulation of multiple metabolic pathways. Clinical investigations indicated that the levels of VNN1 were increased in the urine and blood of diabetic patients, but the physiological significance of this phenomenon remains unknown.In this study, we demonstrated that the hepatic expression of VNN1 was induced in fasted mice or mice with insulin resistance. Gain-and loss-of-function studies indicated that VNN1 increased th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
58
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(63 citation statements)
references
References 51 publications
5
58
0
Order By: Relevance
“…Vanin-1 has been noticed to be upregulated before other traditional markers in a rat model of colitis-induced renal injury [47] and prior to albuminuria in a rat model of spontaneous T2D [40]. It has been demonstrated that increased vanin-1 expression in various disorders including diabetes, contributed to elevated hepatic glucose production, thereby upregulation of gluconeogenic genes resulting in worsening hyperglycemia [48]. In addition, decreased vanin-1 activity improves glucose tolerance and insulin sensitivity in an animal model of T2D [49].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vanin-1 has been noticed to be upregulated before other traditional markers in a rat model of colitis-induced renal injury [47] and prior to albuminuria in a rat model of spontaneous T2D [40]. It has been demonstrated that increased vanin-1 expression in various disorders including diabetes, contributed to elevated hepatic glucose production, thereby upregulation of gluconeogenic genes resulting in worsening hyperglycemia [48]. In addition, decreased vanin-1 activity improves glucose tolerance and insulin sensitivity in an animal model of T2D [49].…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, vanin-1 has been found to be involved in oxidative stress and inflammatory processes by releasing cysteamine [48], which suppresses the activity of antioxidants including SOD and GSH, thereby creating oxidative stress status [16]. In addition, vanin-1-deficient mice displayed cysteamine activity loss with subsequent activation of γ-glutamylcysteine synthetase that leads to elevated GSH stores, an important protecting enzyme against oxidative stress-induced tissue damage [50].…”
Section: Discussionmentioning
confidence: 99%
“…One way in which vanin 1 promotes this inflammatory reaction and intestinal injury is by decreasing the activity of -glutamylcysteine synthetase and thereby decreasing the stores of reduced glutathione (Berruyer et al, 2004;Martin et al, 2004). Additionally, vanin 1 is strongly induced by fasting: Chen and coworkers have shown that it activates gluconeogenesis and increases glucose output in hepatic cells and that this is mediated through the Akt signalling pathway (Chen et al, 2014).…”
Section: Introductionmentioning
confidence: 97%
“…Furthermore, vanin-1 was reported to be involved in cardiovascular diseases [22], [23]. Overexpression of vanin-1 was associated with progression to chronic pediatric immune thrombocytopenia (ITP) [24], and was shown to lead to hyperglycemia [25]. Vanin-1 −/− mice showed protective effects against a variety of phenotypes, such as oxidative stress [26], intestinal inflammation [27], and colon cancer [28], mostly due to higher glutathione storage to maintain a more reducing environment.…”
Section: Introductionmentioning
confidence: 99%